Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar Siswa Kelas III Pada Pembelajaran IPAS - Zohrah Zohrah; Sarbanun Boy (Jurnal Pembelajaran dan Pendidikan Dasar, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on learning outcomes in the IPAS subject for Grade III students at SDN 02 Suntalangu in the 2024/2025 academic year. The total population consisted of 167 students, and the sampling technique used was total sampling, involving all students from class III A and III B, totaling 35 students. This research is a Quasi-Experimental Design using the Nonequivalent Control Group Design. Data were collected through multiple-choice tests and analyzed using SPSS 30 software. The results of this study indicate that there is no significant effect of the CTL learning model on students' learning outcomes in the IPAS subject for Grade III at SDN 02 Suntalangu. This is evidenced by the hypothesis test result using a Two-Sided test, where p = 0.054, which is greater than 0.05.